The Impact Of Narrative Images To Create Awareness About Environmental Degradation In Kafanchan City, Nigeria - Timothy, Titus (2024)
The environment in kafanchan city, nigeria heavily deteriorates every day due to human factors such as refuse dumping, bush burning, deforestation, and open grazing. Therefore, this study employs narrative images to raise awareness of the degradation problems occurring in the city by using photography. Photography has proven to be an essential medium of visual communication to raise awareness, but its potential is not fully utilised in nigeria. Hence, this study is qualitative and utilizes an exploratory research design in its approach. The data was collected by using the stratified sampling method by interviewing two groups of people, civil servants, and non-government workers. Analysis of the data was done by using thematic and visual narrative methods. A simple percentage was used to calculate whether the images were effective in conveying environmental degradation messages based on a 3-point likert scale. The likert scale was used to add value to the qualitative research. Findings from the respondents indicate that the images have a very strong impact in conveying environmental degradation messages. This shows that environmental degradation messages can be effectively conveyed through narrative images in the form of photographs. As an outcome of this research, the photobook tells a story and increases awareness about environmental degradation. This study is a call to action towards the conservation of the environment in kafanchan city nigeria. Recommendations were also made for future studies in the field.